Role of Sorption Isotherms in the Analysis of Coupled Heat and Mass Fluxes in Porous Media - Reis, A. Heitor (2005)
The aim of this work is to show the importance of the sorption isotherms in the study of the heat and mass fluxes in unsaturated porous media. General forms of the heat and mass fluxes are presented in terms of experimentally accessible quantities. The role of the isotherm slope in the coupling of heat and mass fluxes and its influence on the effective permeability are shown. Separate relations for vapor and liquid fluxes through the porous medium are presented as functions of the temperature and the isotherm slopes. Nonstationary isothermal mass flux is also analyzed, a relaxation time for this process is identifled, and its relation to the isotherm slope is also discussed.